Evaluation of quality of life and use of photobiomodulation in the management of pain in a patient with Eagle's Syndrome: A case report (Research, Society and Development, 2025)
Eagle's Syndrome (ES) is characterized by the manifestation of the symptomatology caused by an abnormal elongation of the styloid process or calcification of the stylohyoid ligament. The condition is rare, with a probable multifactorial etiology, affecting a small percentage of the population and its symptoms include odynophagia, dysphagia, orofacial pain and a foreign body sensation in the throat. Diagnosis is made through clinical assessment and imaging tests, and treatment is traditionally performed either surgically or conservatively, with the possibility of using photobiomodulation. This study aimed to report the case of a 53-year-old Brazilian woman diagnosed with ES who was seen at the Orofacial Pain Control Service of the Hospital Universitário Lauro Wanderley (HULW) in João Pessoa-PB. Epidemiological and clinical data and the patient's Quality of Life (QoL) were analyzed, with information collected through in-person questionnaires, and then compared with existing literature. In addition, the application of photobiomodulation using Light Emitting Diode (LED) was analyzed in 10 sessions as a complementary treatment for pain management in a patient with ES and its intensity was assessed before and after the sessions using the Visual Analogue Pain Scale (VAS). The analysis of the data obtained was consistent with the literature and suggests the multifaceted nature of the impact of ES on a patient's QoL. The LED therapy intervention seemed to improve aspects of the physical domain, but the data collected should be interpreted with caution due to the limitations of the study. It is concluded that LED therapy had beneficial effects in reducing pain in the patient and highlighted the potential efficacy of photobiomodulation as a promising intervention for pain management in SE.